Literature Review: Pengaruh Jus Mentimun terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi - Putri, Azzizah Adelia; Khrisna, Lucia Firsty Puspita (Maternal & Neonatal Health Journal, 2025)
Hypertension is one of the most common health problems in the elderly and is known as the "Silent Killer" because it often shows no symptoms until serious complications occur. One of the non-pharmacological therapies that can be given to hypertensive patients is cucumber juice. Cucumber juice contains potassium or potassium substances contained in cucumbers have the function of controlling blood pressure and are part of the electrolyte element. To find out the effect of cucumber juice can lower blood pressure in the elderly with hypertension. This study used a literature review method for five journals obtained through a systematic search using Google Scholar with inclusion and exclusion criteria. All five journals showed that cucumber juice was able to lower blood pressure in the elderly with hypertension. There is an effect of cucumber juice on the reduction of blood pressure in the elderly with hypertension.